Development status and prospects of egg products industry in China - Sasa Liu; Yao Yao; Na Wu; Shuping Chen; Lilan Xu; Yan Zhao; Yonggang Tu (Food Science of Animal Products)
As a kind of food rich in high-quality protein, poultry eggs not only play the most basic nutritional role in national life, but also widely used in bread, pastry, baking and other food industry because of its excellent processing characteristics such as foaming, emulsification and gel properties, besides its active ingredients can also develop new egg products and functional foods. China, a large country producing and consuming of poultry eggs, has ranked first in the annual production of poultry eggs since 1985. However, the consumer market is dominated by fresh eggs, whose processing conversion rate is only about 12%, and it is mainly based on traditional egg products such as salted eggs and preserved eggs. Compared with Western countries, the market share of egg powder, egg liquid, dry egg products, egg drinks, convenient egg products and other new egg products is small in China. In recent years, China’s egg industry has entered the mature stage of development, which takes a favorable trend. In 2022, the output value of China’s egg processing industry has exceeded 400 billion RMB. This paper mainly updates and interprets the history, present situation and prospect of egg processing industry in China.